Patirūp rabop kānpokkhrō̜ng læ kračhāi ʻamnāt : khō̜sanœ̄ čhāk Wēthī Phākhī Phatthanā Prathēt Thai - Wanwisā Sǣngthim (Khrōngkān Wēthī Phākhī Phatthanā Prathēt Thai, Sathāban Chumchon Thō̜ngthin Phatthanā, 2014)
Reformation in the government system and decentralization of the government in Thailand.